Metabolomic Insights into Sexual Multi-Morphism of Sinomenine Accumulation in Sinomenium acutum - Yanxian Luo; Wen Xu; Yanling Fan; Xinyu Ma; Qian Deng; Meng Li; Wei Sun (Plants, 2025)
Sinomenium acutum is the main raw material for sinomenine. Empirical evidence indicates a marked disparity in sinomenine content among S. acutum plants with different genders, resulting in varying medicinal potential of the processing products. However, the mechanism underlying gender-determined differences in sinomenine accumulation is still elusive. In this study, untargeted metabolomics was performed among female, male, and undifferentiated S. acutum plants. In total, 1213 metabolites were identified, and most of them vary in the roots but not in the leaves among the different genders. Integrated correlation analysis on the DAMs (differentially accumulated metabolites) enriched in the isoquinoline alkaloid biosynthesis pathway suggests coclaurine as an intermediate determining gender-dependent sinomenine variation. Furthermore, hormonal profiling revealed 34 endogenous phytohormones exhibiting significant gender-based discrepancy in the roots. Among these, ABA (abscisic acid) and 5-DS (5-deoxystrigol) show significant positive correlation with sinomenine content. Then, exogenous ABA with gradient concentration was applied on S. acutum plants, and the sinomenine content in the roots increased from 31% to 166% under treatment. Our findings demonstrate that coclaurine might serve as a pivotal intermediate during sinomenine biosynthesis in S. acutum. Meanwhile, it is speculated that ABA is a key factor regulating different sinomenine accumulation, which provide a potential method to improve the yield of sinomenine.